Effects of Short-Term Lower Limb Immobilization on Skeleton Muscle Function and Morphology in Men and Women - Yasuda, Nobuo (My University, 2005)
The purpose of this study was to determine the effects of short-term (14d) unilateral leg immobilization using a simple knee brace (60° flexion)/crutchmediated model on muscle function and morphology in men (M, N=13) and women (W, N=14). Isometric and isokinetic (concentric SLOW, 0.52 rad•s-1 and FAST, 5.24 rad•s-1) knee extensor peak torque was determined at three time points (PRE, DAY -2, and DAY -14). At the same time points, magnetic resonance imaging was used to measure the cross-sectional area of the quadriceps femoris and DEXA scanning was used to calculate leg lean mass. Muscle biopsies were taken from vastus lateralis at PRE and DAY-14 for myosin ATPase and myosin heavy chain analysh Women showed greater decreases (PRE vs. DAY-14) compared to men in specific strength (N•cm-2) for isometric (M=3.1±13.3, W=17.1±15.9%; p= 0.055, [mean±SD]) and concentric SLOW (M=4.7±11.3, W=16.6±18.4%; p<0.05) contractions. There were no immobilization-induced sex-specific differences in the decrease in quadriceps femoris cross-sectional area (M=5.7±5.0, W=5.9±:5.2%) or leg lean mass (M=3.7±4.2, W=2.7±2.8%). There were no fiber type transformations, and the decrease in Type I (M=4.8±5.0, W=5.9±3.4%), IIa (M=7.9±9.9, W=8.8±8.0%) and Ilx (M=10.7±10.8, W=10.8±12.1 %) fiber areas was similar between sexes. These findings indicate that immobilization-indt: ced loss of knee extensor muscle strength is greater in women compared tc men in spite of a similar extent of atrophy at the myofiber and whole muscle levels after only 14d of unilateral leg immobilization. Furthermore, we have described an effective and safe method of knee immobilization that results in significant reductions in quadriceps muscle strength and fiber size.
Keywords: lower limb immobilization; skeletal muscle function; morphology